Mirʾāt al-waqāyiʿ-i Muẓaffarī. Volume 2 - Sipihr, ʿAbd al-Ḥusayn Khān Lisān al-Salṭanah, (Miras Maktoob, ISBN: 9789004365452., 2019)
ʿAbd al-Ḥusayn Khān Lisān al-Salṭanah Sipihr (1869-1933), also known by his honorific title of Malik al-Muwarrikhīn, was an historian, a court official, a chronicler, a politician, a writer of many books in various disciplines, and an Iranian newspaperman of the first hour. Entering the secretarial ranks of the court at the age of eighteen, he held various positions of trust under Nāṣir al-Dīn Shāh (d. 1313/1896) and Muẓaffar al-Dīn Shāh (d. 1907). After Muẓaffar al-Dīn Shāh's death he worked in several official capacities, lastly as head of the religious endowments of Kashan. Unable to make a living as a publisher, he spent the last part of his life in education. He died after a short illness in Tehran, aged 64. This volume contains his thusfar unpublished chronicle of the reign of Muẓaffar al-Dīn Shāh. His reports on Iran's internal affairs are especially interesting since he was a close witness of most of these events. 2 vols; volume 2.